The relationship between cognitive function and muscle mass in older adults: a longitudinal study based on CLHLS - Yin Shi; Yin Shi; Yu Zhang; Xinyu Yang; Jiali Yang; Shilang Wang; YanFang Hong (Frontiers in Psychiatry)
BackgroundSarcopenia is the main cause of disability in an aging society and increases the risk of death in older adults. However, the relationship between cognitive function and muscle mass and the underlying mechanisms are not clear. This study aims to investigate the relationship between cognitive function and muscle mass in the older adults.MethodsThis study was based on the Chinese Longitudinal Healthy Longevity Survey (CLHLS), phase III from 2011 to 2018. We analyzed 2536 participants aged ≥60 years. SPSS 27.0 software was used for data screening and statistical analysis, and MPLUS 8.7 and R4.4.2 software were used to construct cross-lag models and restricted cubic splints.ResultsIn this study, out of 2,536 participants, there were 1,283 males (50.6%) and 1,253 females (49.4%), with an average age of 77.54 ± 8.6 years. Correlation analysis showed that cognitive function was positively correlated with muscle mass in older adults. At all time points (P<0.05). The cross-lag model revealed a one-way prediction effect: The path coefficients of ASMI→MMSE in T1→T2 and T2→T3 were statistically significant in the general population, men and women (P<0.05), and the path coefficients β were all greater than 0. The association of MMSE → ASMI was significant only at the T2 → T3 time point in the overall population (β = 0.010, P < 0.05), and not statistically significant at T1 → T2 and T2 → T3 time points in both males and females (P <0.05). RCS results showed that the association between skeletal muscle mass and cognitive impairment in the total population (Poverall trend <0.05, Pnon-linear <0.05), older men (Poverall trend <0.05, Pnon-linear <0.05) and older women (Poverall trend <0.05, Pnon-linear <0.05) showed a nonlinear increasing trend. It is suggested that ASMI should be maintained at 7.45kg/m2 and 5.68kg/m2 or above in older men and women, respectively.ConclusionMuscle mass had a major predictive effect on cognitive trajectory, especially in females. Maintaining ASMI above gender-specific thresholds may help slow cognitive decline, suggesting that muscle mass can serve as an adjustable biomarker for dementia prevention. Longitudinal studies should verify the validity of these thresholds in different populations.